Effects of depression and exercise on health-related quality of life in patients with Parkinson's disease. (September 2020) - Koutsouras, George W; Levine, Kimberly; Duroseau, Nathalie; Ciraco, Christina; Chan, Vivian; Pergament, Kathleen; Chan, Thomas; Mancini, Jayme D; Leder, Adena N; Krishnamachari, Bhuma
Objectives: There is limited literature describing the effect exercise may have on depression and an individual's health-related quality of life (HRQoL) in Parkinson's Disease (PD). We aim to quantify this effect. Methods: A cross-sectional questionnaire was administered to 60 PD subjects. The Parkinson's Disease Questionnaire-39 (PDQ-39) summary index and the Geriatric Depression Scale-30 were used to quantify HRQoL and depression, respectively. Data were obtained on exercise habits. ANOVA and multivariate linear regression analysis were used to calculate mean differences in HRQoL. Results: Depression was consistently related to HRQoL ( p  < 0.05). Of those who exercised as an adult before PD diagnosis, 49.02% ( n  = 25) reported depression as compared to 88.89% ( n  = 8) of those who did not report adult exercise ( p  = 0.03). Those who exercised frequently as an adult prior to PD diagnosis had a better PDQ-39 Cognitive Index ( p  = 0.03). Those who were not depressed and were currently exercising had a significantly higher HRQoL than those who were depressed and did not exercise ( p  < 0.01). Discussion: Exercising and depression may interact to affect HRQoL. Thus, coordination of mental health evaluation and exercise regimens in persons with PD may improve HRQoL.